The Associated Students of California Polytechnic School extend a cordial invitation to you to attend the Decennial Celebration of the School - Frank Aston::::::photographer::: (1913)
Invitation from 'The Associated Students of California Polytechnic School extend a cordial invitation to you to attend the Decennial Celebration of the School.'